Kommunale Smart-City-Ansätze als Treiber nachhaltiger urbaner Transformationen? - Koch, Florian (My University, 2021)
|The article analyses the link between sustainability transformations and smart-city approaches in German cities. Here existing research into the process of digitalisation in German municipalities are evaluated and links to sustainable urban development traced. The analysis focuses on whether smart-city actors can serve as pioneers of a sustainability transformation and on the fields of action in which smart-city activities are anchored. In the course of the article it becomes clear that digitalisation and smart-city approaches have the potential to support sustainability transformations on the level of the cities. However, to date references to sustainability in smart-city strat-egies tend to be lip service rather than providing a strategic instrument for great transformation. Orienting smart-city strategies towards sustainable development goals would, however, offer actors an adequate framework to create sustainable and smart cities.

Der Beitrag analysiert die Verbindung zwischen Nachhaltigkeitstransformationen und Smart-City-Ansätzen in deutschen Städten. Hierzu werden bestehende Studien zum Prozess der Digitalisierung in deutschen Kommunen ausgewertet und die Bezüge zu einer nachhaltigen Stadtentwicklung aufgezeigt. Schwerpunkt der Analyse ist die Frage, ob Smart-City-Akteure als Pioniere des Wandels zu mehr Nachhaltigkeit dienen können und in welchen Handlungsfeldern Smart-City-Aktivitäten verankert sind. Im Rahmen des Beitrags wird deutlich, dass Digitalisierung und Smart City durchaus Potenziale bieten, um Nachhaltigkeitstransformationen auf Ebene der Städte zu unterstützen. Bislang ist der Nachhaltigkeitsbezug in Smart-City-Strategien jedoch eher Lippenbekenntnis und weniger strategisch eingesetztes Instrument für eine große Transformation. Eine Ausrichtung von Smart-City-Strategien an den Sustainable Development Goals (SDGs) böte den Akteuren jedoch einen adäquaten Rahmen, um nachhaltige und smarte Städte zu schaffen.
Keywords: Smart City; Nachhaltige Stadtentwicklung; Kommunalentwicklung; Digitalisierung; Stadtplanung; Transformation